2016
DOI: 10.1126/science.aah5143
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methyltransferase DNMT3C protects male germ cells from transposon activity

Abstract: DNA methylation is prevalent in mammalian genomes and plays a central role in the epigenetic control of development. The mammalian DNA methylation machinery is thought to be composed of three DNA methyltransferase enzymes (DNMT1, DNMT3A, and DNMT3B) and one cofactor (DNMT3L). Here, we describe the discovery of Dnmt3C, a de novo DNA methyltransferase gene that evolved via a duplication of Dnmt3B in rodent genomes and was previously annotated as a pseudogene. We show that DNMT3C is the enzyme responsible for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
276
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(297 citation statements)
references
References 53 publications
16
276
0
5
Order By: Relevance
“…DNA methylation in promoter regions is correlated with transcriptional repression. Important regulators of DNA methylation include the writers (DNMT1 (maintenance methylation through DNA replication cycle), DNMT3A, DNMT3B, and DNMT3C (Barau et al, 2016) (de novo methyltransferases)), a cofactor without catalytic activity DNMT3L, and erasers (TET1–3). A distinct feature of DNA methylation in brain is that neurons are enriched in mCH (non‐CG methylation, H = A/C/T) and 5‐hydroxymethylcytosine (5hmC, established by TETs in the first of a series of stepwise modifications (Ito et al, 2011)).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…DNA methylation in promoter regions is correlated with transcriptional repression. Important regulators of DNA methylation include the writers (DNMT1 (maintenance methylation through DNA replication cycle), DNMT3A, DNMT3B, and DNMT3C (Barau et al, 2016) (de novo methyltransferases)), a cofactor without catalytic activity DNMT3L, and erasers (TET1–3). A distinct feature of DNA methylation in brain is that neurons are enriched in mCH (non‐CG methylation, H = A/C/T) and 5‐hydroxymethylcytosine (5hmC, established by TETs in the first of a series of stepwise modifications (Ito et al, 2011)).…”
Section: Molecular Links Between Aging and Admentioning
confidence: 99%
“…Very recently, one study identified a new de novo DNA methyltransferase DNMT3C in murine germ cells. DNMT3C exhibits high identity with DNMT3B, and is specialized at methylating the young retrotransposons [7]. Beside the above-mentioned enzymes, which are essential for the methylation of mammalian DNA, the DNMT family also includes two additional members, DNMT2 and DNMT3L.…”
Section: Introductionmentioning
confidence: 99%
“…Mice deficient in either Dnmt1 or Dnmt3b exhibit embryonic lethality [9, 10]. Male mice without Dnmt3c are sterile [7]. Thus, these phenotypes demonstrate that the establishment and maintenance of global genomic methylation processes is the basis for cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Deborah Bourc'his (Institut Curie, France) reported a new member of the DNA methyltransferase (Dnmt) family, Dnmt3c, which selectively targets the promoter of evolutionarily young retrotransposons and only during spermatogenesis. This gene specifically evolved in rodents by tandem duplication of Dnmt3b (Barau et al, 2016). This raises the question of how the male germline of humans and other non-rodent mammals controls retrotransposons.…”
Section: Epigenetics and Hereditymentioning
confidence: 99%